Pharmacologic inhibition by spironolactone attenuates experimental abdominal aortic aneurysms - Ladd, Zachary; Su, Gang; Hartman, Joseph; Lu, Guanyi; Hensley, Sara; Upchurch, Gilbert R.; Sharma, Ashish K. (Frontiers in Cardiovascular Medicine, 2023)
Background: Abdominal aortic aneurysms (AAA) are characterized by vascular inflammation and remodeling that can lead to aortic rupture resulting in significant mortality. Endothelial cell-dependent pannexin-1 channels can modulate ATP secretion to regulate the pathogenesis of AAA formation. Our hypothesis focused on potential of spironolactone to inhibit endothelial cell-mediated ATP release for the mitigation of AAA formation. Methods: A topical elastase AAA model was used initially in C57BL/6 (wild-type; WT) male mice. Mice were administered either a vehicle control (saline) or spironolactone and analyzed on day 14. In a second chronic AAA model, mice were subjected to elastase and β-aminopropionitrile (BAPN) treatment with/without administration of spironolactone to preformed aneurysms starting on day 14 and analyzed on day 28. Aortic diameter was measured by video micrometry and aortic tissue was analyzed for cytokine expression and histology for immune cell infiltration and elastic fiber disruption. In vitro studies were performed to evaluate the crosstalk between endothelial cells, macrophages and smooth muscle cells. Results: In the murine elastase AAA model, elastase-treated WT mice administered with spironolactone had a significant decrease in aortic diameter compared to elastase-treated controls on day 14. A significant decrease in elastic fiber disruption and immune cell (macrophages and neutrophils) infiltration as well as increase in smooth muscle -actin expression occurred in mice treated with spironolactone compared to untreated controls. Spironolactone treatment also significantly mitigated pro-inflammatory cytokine expression, especially IL-1 and HMGB1, in the aortic tissue compared to untreated controls. Moreover, in the chronic AAA model, spironolactone treatment of preformed aneurysms significantly attenuated aortic inflammation, vascular remodeling and AAA formation compared to untreated controls on day 28. Mechanistically, in vitro data demonstrated that spironolactone treatment attenuates extracellular ATP release from endothelial cells to mitigate macrophage activation via P2X7 receptors and smooth muscle cell-dependent vascular remodeling via P2Y2 receptors. Conclusion: These results suggest the therapeutic potential of spironolactone to mitigate aortic inflammation and remodeling to attenuate AAA formation as well as decrease growth of preformed aneurysms.